2 μm Ultrabroad spectra and laser operation of Tm:GdScO3 crystal. (November 2021) - Li, Shanming; Fang, Qiannan; Zhang, Yuhang; Tao, Siliang; Zhang, Junxuan; Quan, Cong; Sun, Dunlu; Zhao, Chengchun; Hang, Yin
Highlights: Continuous-wave laser operation at 2 μm of Tm:GdScO3 crystal were investigated. Tm 3+ : 3 F4 → 3 H6 (2 μm) of Tm:GdScO3 crystal exhibits broadband of 269 nm. Tm:GdScO3 crystal is promising for broadband tunable and ultrafast lasers. Abstract: Spectra and laser operation at 2 μm of Tm:GdScO3 crystal are investigated for the first time. The low symmetry in GdScO3 crystal broadens emission spectrum (269 nm) of Tm 3+ : 3 F4 → 3 H6 transition, which is the widest in Tm 3+ doped crystals. The emission cross-sections at 1975 nm are approximately 0.23 (E//X), 0.23 (E//Y) and 0.28 (E//Z) × 10 -20 cm 2, respectively. The fluorescence lifetime of Tm 3+ : 3 F4 is 3.68 ms. Pumped by a 793 nm laser diode, the output power yields 4.53 W with the slope efficiency of 25%. All results indicate Tm:GdScO3 a promising candidate for 2 μm tunable and ultrashort lasers.